Attitudes towards depression of Argentinian, Chilean, and Venezuelan healthcare professionals using the Spanish validated version of the revised depression attitude questionnaire (SR-DAQ) - Genesis Camacho-Leon; Marco Faytong-Haro; Keila Carrera; Ivonne De la Hoz; Robert Araujo-Contreras; Karelis Roa; Hans Mautong; Jhoselena Cardozo; Marianny Briceño; Ivan Cherrez-Ojeda (Elsevier, 2022)
Background: The beliefs and attitudes of physicians toward depression may predict whether they are supportive or avoidant of patients diagnosed with this condition. Describing the attitudes toward depression of Argentinian, Chilean, and Venezuelan healthcare professionals could be a valuable tool for understanding the Latin American perspective on depression recognition, management, and prevention. Materials and methods: A cross-sectional study was conducted among healthcare professionals in Argentina, Chile, and Venezuela using the Spanish validated version of the revised depression attitude questionnaire (R-DAQ). The questionnaire was collected online from August to November 2021, in a quota-based sample of 1759 health professionals (the final analytical sample is 1234). Descriptive data analyses were performed using STATA version 16 statistical software. Results: Depression was considered a disease that anyone could suffer by 90% of the respondents. However, 70% of professionals answered that they feel more comfortable dealing with physical illness than mental illness. Furthermore, the findings show that a quarter of the participants in the study believed that either medical treatment (28.6%) or psychosocial approach (<20%) were ineffective tools for people suffering from depression. Findings also show that depression is seen as a more natural part of life by Argentinian professionals and men. Finally, psychologists and psychiatrists are most likely to treat depression as any other physical disease. Medical providers who routinely perform surgeries are not as likely to know how to treat depression or consider it an actual disease. Conclusions: Healthcare professionals in Argentina, Chile, and Venezuela have varying attitudes toward depression. While they recognize depression as a disease on the same level as other physical diseases, most do not know how to treat it. The findings point to the need for these countries to promote the training of healthcare workers in areas such as depression diagnosis, treatment, and social interventions.